Hukum Transaksi Online dari Perspektif Fiqih Kontemporer - Yeti Dewanti; Devi Oktaviani; Yopita Sari; Ibrahim Hoesein; Mufida Jihan; Yela Dewi Ningsih; Pajri Satrio Azhari (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
The development of digital technology has transformed the global economic landscape through the proliferation of online trading practices. This study aims to analyze the law of online transactions from the perspective of contemporary fiqh by examining muamalah principles, the validity of digital contracts, clarity of transaction objects, and their relevance to maqāṣid al-syarī'ah. The research method used is library research with a qualitative approach, analyzing classical and contemporary fiqh literature, DSN-MUI fatwas, and digital transaction regulations. The results show that online trading is considered valid under Islamic law as long as it fulfills the elements of mutual consent (tarāḍin), honesty, information transparency, and object clarity. Digital contracts through approval clicks or electronic messages are categorized as al-bay' bi al-mu'āṭah, which is valid in fiqh. Consumer protection features such as refund, return, and escrow systems on marketplaces align with the concept of khiyār. From the perspective of maqāṣid al-syarī'ah, digital transactions are permissible as long as they bring benefits and are free from gharar, tadlīs, and data exploitation. This study affirms that Islamic fiqh is dynamic and adaptive to modern digital technological developments.